Suzuki coupling of aroyl-MIDA boronate esters – A preliminary report on scope and limitations. (22nd June 2021) - Lai, Samson; Takaesu, Noah; Lin, Wen Xuan; Perrin, David M.
Graphical abstract: Highlights: Aroyl-MIDA boronate esters are now substrates for Suzuki-Miyaura Cross-coupling. Coupling proceeds in moderate yield to afford a variety of ketones. Reaction scope is limited to aroyl-MIDA-boronates. Acyl-MIDA-boronates undergo proto-deborylation. Short reaction time under ambient biphasic conditions at high catalyst loading. Abstract: Recent methodological reports for synthesizing acyl-MIDA boronate esters compel an investigation of their potential use as substrates in a standard Suzuki-Miyaura cross-coupling reaction. Here we report the production of benzophenones by CC cross coupling between a benzoyl-MIDA boronate ester and a multitude of aryl bromide substrates in adequate yields following optimization under ambient conditions outside of a glove box. Under these standard conditions, none of several acyl-MIDA boronate esters (in an alkyl series) serves as a competent coupling partner. The substrate scope is also limited by the finding that the corresponding trifluoroborates of both acyl- and aroyltrifluroborates are not suitable substrates. For reasons of availability and synthetic difficulty in procuring other aroyl-MIDA boronates, this preliminary study examines the reactivity of benzoyl-MIDA boronate with several aryl bromide substrates.